2011
DOI: 10.1021/es102316m
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated Transport of 2,2′,5,5′-Polychlorinated Biphenyl and Phenanthrene by Fullerene Nanoparticles through Sandy Soil Columns

Abstract: The potential environmental implications of buckminsterfullerene (C60) and its derivatives have received much attention. In this study, we investigated facilitated transport of 2,2',5,5'-polychlorinated biphenyl (PCB) and phenanthrene by nC60 (a stable aqueous-phase aggregate of C60) through two sandy soil columns. We found that low-level (from 1.55 to 12.8 mg/L) nC60 could significantly enhance the mobility of PCB and phenanthrene. However, none of the three model dissolved organic matters (DOMs)-a humic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 37 publications
1
81
0
Order By: Relevance
“…For example, under typical environmental conditions, highly hydrophobic organic contaminants, such as polychlorinated biphenyls and polycyclic aromatic hydrocarbons, sorb strongly to soil organic matter and therefore have very limited mobility in subsurface environments. In a recent study [16], we observed that trace amounts of nC 60 (less than 2 mg/L) resulted in the breakthrough of 2,2 0 ,5,5 0 -polychlorinated biphenyl (PCB) and phenanthrene through saturated soil columns within a few pore volumes (PVs), which vastly differed from what was expected based on conventional theories in that such significant transport enhancement of PCB or phenanthrene should not occur unless the concentrations of colloidal materials are very high (on the order of several hundred mg/L or higher) [18]. Thus, it is evident that the contaminant-mobilizing capability of nC 60 is far greater than those of natural colloids, such as dissolved organic matter.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…For example, under typical environmental conditions, highly hydrophobic organic contaminants, such as polychlorinated biphenyls and polycyclic aromatic hydrocarbons, sorb strongly to soil organic matter and therefore have very limited mobility in subsurface environments. In a recent study [16], we observed that trace amounts of nC 60 (less than 2 mg/L) resulted in the breakthrough of 2,2 0 ,5,5 0 -polychlorinated biphenyl (PCB) and phenanthrene through saturated soil columns within a few pore volumes (PVs), which vastly differed from what was expected based on conventional theories in that such significant transport enhancement of PCB or phenanthrene should not occur unless the concentrations of colloidal materials are very high (on the order of several hundred mg/L or higher) [18]. Thus, it is evident that the contaminant-mobilizing capability of nC 60 is far greater than those of natural colloids, such as dissolved organic matter.…”
Section: Introductionmentioning
confidence: 93%
“…Column experiments were conducted using a previously developed protocol [16]. Soil was dry-packed into Omnifit borosilicate glass columns (10 Â 0.66 cm; Bio-Chem Valve) with 10-mm stainless-steel screens (Valco Instruments) on both ends.…”
Section: Column Experimentsmentioning
confidence: 99%
See 3 more Smart Citations